Eye wall resections for intraocular tumors: Our experience - Tandava Krishnan; Lingam Gopal; Jyotirmay Biswas; Prema Padmanabhan; Vikas Khetan (Indian Journal of Ophthalmology, 2014)
We conducted a retrospective review of 11 eyes undergoing eye wall resection between October 1998 and October 2009. The median age of 11 patients was 29 years. Decreased vision (eight) was the most common presenting symptom. Ciliary body medulloepithelioma was the most common clinical diagnosis (six). Medulloepithelioma was the most common histopathological diagnosis (four). The duration of follow-up ranged from 0.5 to 67 months (median 11 months). Three eyes needed to be enucleated in the postoperative period (margin involvement two eyes, recurrence one eye). Postoperative complications among others included retinal detachment (three), vitreous hemorrhage (three), cataract (two), and suprachoroidal hemorrhage (two). To conclude, prognosis of this procedure continues to be guarded needing close postoperative follow-up.